2010
DOI: 10.1016/j.biopsych.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 5/Homer Interactions Underlie Stress Effects on Fear

Abstract: Background-Glutamatergic transmission is one of the main components of the stress response, nevertheless, its role in the emotional stress sequelae is not known. Here, we investigated whether interactions between group I metabotropic glutamate receptors (mGluR1 and mGluR5) and Homer proteins mediate the delayed and persistent enhancement of fear induced by acute stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 44 publications
2
54
0
Order By: Relevance
“…We also observed a significant decrease in Homer1/mGluR5 coupling following chronic social defeat. This effect cannot be specified to either Homer1 splice variant at the moment because of the lack of specific and reliable antibodies targeting Homer1a (Tronson et al, 2010). Further studies will be required to unravel the functional consequence of this effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed a significant decrease in Homer1/mGluR5 coupling following chronic social defeat. This effect cannot be specified to either Homer1 splice variant at the moment because of the lack of specific and reliable antibodies targeting Homer1a (Tronson et al, 2010). Further studies will be required to unravel the functional consequence of this effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the late onset of therapeutic effects as well as unsatisfactory relapse rates and side effects illustrates the need for improved therapeutics (Thase, 2006). Recent studies have provided convincing evidence that dysregulation of glutamate signaling, mainly via its postsynaptic receptors a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), N-methyl-D-aspartate (NMDA), and metabotropic glutamate receptors (mGluRs), contributes to the emergence of psychiatric disorders (Kendell et al, 2005;Sanacora et al, 2012;Mathews et al, 2012;Yim et al, 2012;Tronson et al, 2010). Modulation of glutamate receptor function has therefore been proposed as a promising target for antidepressant, anxiolytic, and antipsychotic drug development .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence exists for effects of both a single restraint event and repeated restraints on subsequent fear learning. Several studies have shown increased freezing upon exposure to a context previously paired with shock in rodents that have undergone brief (30 min-2 h) restraint (Cordero et al 2003;Rodriguez Manzanares et al 2005;Tronson et al 2010), whereas other studies utilizing repeated restraint have observed increased freezing upon exposure to a tone previously paired with shock (Meyer et al 2014;Suvrathan et al 2014;Baratta et al 2015). The degree to which restraint stress affects fear learning, generalization, extinction rate, or extinction retention differs, depending on the method and duration of restraint, the varying delays between the stress and fear conditioning and differences in the amount of shock utilized during conditioning (Miracle et al 2006;Andero et al 2011Andero et al , 2013Chauveau et al 2012).…”
Section: Stress-enhanced Fear Learning Modelsmentioning
confidence: 99%
“…Several recent reviews have covered the broad array of neurobiological players that have been found to mediate SEFL, such as glucocorticoids, glutamate, glycine, and cytokines (Cordero et al 2003;Akirav and Maroun 2007;Iwamoto et al 2007;Kohda et al 2007;Yamamoto et al 2009;Tronson et al 2010;Jones et al 2015;Maren and Holmes 2016;Perusini et al 2016). However, in spite of the contribution of epigenetic mechanisms to stress and numerous aspects of fear memory independently, very little work has been done in the realm of epigenetics at the crossroads between stress and fear memory.…”
Section: The Neuroepigenetics Of Stress-enhanced Fear Learningmentioning
confidence: 99%